KELENTENG CIN BUK KIONG, PULAU RUPAT - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2006)
Generaly, the Chinese Temple is a place for Chinese people doing their religious activities, e.g. pray God, anchestor, prophet and the soul related with Konfusianism, Taoism and Buddhism. The name of some Chinese Temples use their main god or god's superiority. It's interested in analyzing the architecture of the building of Chinese Temple because of its uniqueness